2024
DOI: 10.3390/ma17102396
|View full text |Cite
|
Sign up to set email alerts
|

Method for Determining the Coefficient of Friction Variation Pattern as a Function of Density at Low Temperatures Using the Example of Dry Ice–Steel Contact

Jan Górecki,
Wiktor Łykowski,
Jozef Husar
et al.

Abstract: The developments in manufacturing technologies are expected to reduce energy input without compromising product quality. Regarding the material densification process, numerical simulation methods are applied to achieve this goal. In this case, relevant material models are built using functions that describe the variation in mechanical parameters of the material in question due to its deformation. The literature review conducted for this research has revealed a shortage of experimental research methods allowing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
(51 reference statements)
0
0
0
Order By: Relevance
“…Additionally, in the literature, the authors made available the results of research work on the numerical models developed, where the nature of the change in the values of the material’s mechanical parameters as a function of density, such as Young’s modulus, Poisson’s ratio or coefficient of friction, was determined. For those interested, we recommend the indicated publications [ 19 , 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, in the literature, the authors made available the results of research work on the numerical models developed, where the nature of the change in the values of the material’s mechanical parameters as a function of density, such as Young’s modulus, Poisson’s ratio or coefficient of friction, was determined. For those interested, we recommend the indicated publications [ 19 , 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Since numerous publications [19][20][21] have demonstrated that the mechanical properties of dry ice change with a change in the degree of compaction, the authors decided to reflect these changes through the use of the VUSDFLD subroutine, which defines yield stress values (Table 1) as the criterion determining the change in material properties. This means that the input values of the parameters describing material properties that Abaqus will take for a given calculation step will depend on the determined PEEQ (equivalent plastic stress) values obtained in the previous calculation The material that is being compacted was modelled as a deformable object and the Drucker-Prager/cap (DPC) model was used to describe its mechanical properties.…”
Section: Numerical Model Of DI Compaction Processmentioning
confidence: 99%
See 1 more Smart Citation